Interface Reaction Between BaCo0.7Fe0.2Nb0.1O3-d Membrane and Ni-Based Catalyst - Yang, Zhibin; Zhang, Yuwen; Ding, Weizhong (Asian Journal of Chemistry, 2014)
The interface reaction between BaCo0.7Fe0.2Nb0.1O3-d (BCFNO) membrane and Ni-based catalyst materials were studied by analyzing the different catalyst materials, such as Al2O3, MgO, YSZ and TiO2. XRD and SEM characterization of the BCFNO membrane show that the Al2O3 and TiO2 easily react with BCFNO membrane and form a new phase. The MgO also reacts with BCFNO membrane in long time running, while the reaction is relatively small. However, the YSZ does not react with BCFNO. This provided a way to choose the suitable catalyst materials for membrane reactor during the long time running operation.